Relationship between lipoprotein lipase hindiii polymorphism and lipids in a group of colombian patients with obstructive coronary disease (2014)
HindIII polymorphism is the most common variant in the lipoprotein lipase gene, however, its association with cardiovascular disease is controversial. Objective: To establish the frequency of the HindIII polymorphism and its relationship with lipid profile and coronary arterial disease (CAD) in Colombian patients. Materials and Methods: The sample comprised patients attending a central hemodynamics of Quindío, by necessity of coronary angiography. HindIII polymorphism was evaluated by polymerase chain reaction and enzyme restriction. Results: 389 patients were divided into individuals with CAD = 50% (60.4%) and individuals with EOC <50% (39.6%). Low density lipoproteins cholesterol (LDL-C) was normal, but significantly higher in CAD = 50%. High density lipoprotein cholesterol (HDL-C) was low in both groups. Hind+/+ genotype and Hind+ allele frequency were 55% and 76%, respectively; for Hind+/- genotype was 41.1%, and for Hind-/- genotype and Hind- allele was 3.85% and 24%, respectively, without significant differences between groups. In CAD = 50%, total cholesterol (TC) and LDL-C were higher in allele Hind-, while HDL-C was lower in the Hind+ allele, with significant differences regarding CAD <50% and the same alleles. There were significant differences in triglyceride and very low density lipoprotein cholesterol) (VLDL-C) between genotypes in CAD <50% group. Conclusion: This work shows that even with a normal lipid profile, this population presents coronary obstructive disease, which does not seem to be associated with low levels of HDL-C or the LPL HindIII polymorphism alone, but may be related to the influence of these on lipids.